From PAPI to CAPI: consequences for data quality on the British Household Panel Study - Heather Laurie (University of Essex, Institute for Social and Economic Research (ISER), 2003)
This paper examines the conversion from PAPI to CAPI of the British Household Panel Survey at Wave 9 (1999). The paper describes the procedures adopted by the BHPS and examines the impact of the introduction of CAPI on key variables within the data.
Keywords: 330